2008
DOI: 10.1021/np800460b
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Polyprenylated Xanthones from the Resin of Garcinia hanburyi

Abstract: Twelve new xanthones (1-12), a pair of new natural products (13 and 14), and 18 known related compounds were isolated from the resin of Garcinia hanburyi. The structures of 1-14 were elucidated by detailed spectroscopic analyses. A cytotoxic assay of the isolated compounds revealed that, with the exception of 2, these compounds were active against the HeLa tumor cell line.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 18 publications
(61 reference statements)
0
65
0
Order By: Relevance
“…Compound 2 Tables 1 and 2) of 2 were compared with those of gambogefic acid [9]. The only difference between them was the presence of a OH group at C(13) in 2 instead of a C(12)¼C (13) (14), together with the HMBCs of HÀC (12), HÀC (14), and H-COSY spectrum, supported the structure assignment (Tables 1 and 2).…”
Section: Results Andmentioning
confidence: 60%
“…Compound 2 Tables 1 and 2) of 2 were compared with those of gambogefic acid [9]. The only difference between them was the presence of a OH group at C(13) in 2 instead of a C(12)¼C (13) (14), together with the HMBCs of HÀC (12), HÀC (14), and H-COSY spectrum, supported the structure assignment (Tables 1 and 2).…”
Section: Results Andmentioning
confidence: 60%
“…Natural sources of prenylated caged xanthones. Plants Parts Caged xanthones G. morella (Figure 2) seeds desoxymorellin (1), morellin (2), morellinol (6), dihydroisomorellin (22), moreollin (25), isomoreollin (26) (Adawadkar et al, 1976;Bhat et al, 1964;Kartha et al, 1963;Rao, 1937;Subba et al, 1978) resin isomorellin (3), morellic acid (4), isomorellic acid (5) (Karanjgaonkar et al, 1966;) G. hanburyi (Figure 2) resin desoxymorellin (1), isomorellin (3), morellic acid (4), isomorellic acid (5), isomorellinol (7), morellin dimethyl acetal (8), gambogin (9), gambogic aldehyde (10), gambogic acid (11), epigambogic acid (12), isogambogic acid (13) (Asano et al, 1996;Feng et al, 2008;Han et al, 2006aHan et al, , 2006bHan et al, , 2006cLee & Chen, 2006;Lin et al, 1993;Ollis et al, 1965;Reutrakul et al, 2007;Tao et al, 2009;Wang et al, 2008a) fruits desoxymorellin (1), isomorellin (3), morellic acid (4), isomorellinol (7), gambogic acid (11), 8,8a-epoxymorellic acid (21), dihydroisomorellin (22), isomoreollin B (23), moreollic acid (27), hanburinone (33), forbesione (39), 2-isoprenylforbesione (desoxyqaudichaudione A) (40), desoxygambogenin (43) (Reutrakul et al, 2007;Sukpondma et al, 2005a) whole plant gambogic acid (11), neogambogic acid (35) (Lu et al, 1984) G. forbesii (Figure 2) branches forbesione (39) (Leong et al, 1996) G. gaudichaudii (Figure 3) leaves morellic acid (4), forbesione (39), gaudichaudiones A-H (53-60), gaudichaudiones I-J (61-62), gaudichaudiic acids A-E (63-67) (Cao et al, 1998a(Cao et al, , 1998bWu et al, 2000) barks gaudichaudiic acids F-I (68-71), 7-isoprenylmorellic acid (72) (Wu et al, 2001;Xu et al, 2000 Garcinia hanburyi has been reported as a rich source of cytotoxic caged xanthones. Its orange gum-resin from stem bark, gamboge, is used in Thai traditional medicine as a purgative and an anthelm...…”
Section: Sources and Structure Diversity Of Prenylated Caged Xanthonesmentioning
confidence: 99%
“…These caged xanthones showed cytotoxicity against many of cancer cell lines such as HL-60, SMMC-7221, BGC-83, P-388, P388/ ADR, and HeLa cells (Feng et al, 2007;Tao et al, 2009;Wang et al, a, 2008b). …”
Section: Sources and Structure Diversity Of Prenylated Caged Xanthonesmentioning
confidence: 99%
“…Plants of the genus Garcinia have been reported in the literature to display both anti-HIV and cytotoxicity activity (Tao et al 2009). For instance, G. mangostana gave mangostin, a compound that indicated significant HIV-1 protease inhibition effect (Chen et al, 1996) while G. livingstoneii has been reported to produce gutifferone A, being an anti-HIV compound (Gustafson et al, 1992).…”
Section: Introductionmentioning
confidence: 99%